Abstract - Video case report ACL and PCL distension injury in an MMA fighter - Liska, D.; Spurny, M.; Luptak, J. S. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2026)
Background. Mixed Martial Arts (MMA) is a high-intensity combat sport that exposes athletes to substantial biomechanical stress, often leading to musculoskeletal injuries. Knee injuries, particularly those affecting the anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL), are of significant concern due to their impact on an athlete`s performance and career longevity.